Obstetrics ICU admissions: challenges faced at a tertiary referral centre - Jamal, Shehla; Mehta, Archana; Goel, Neerja; Ahuja, Mayuri; Afreen, Naima; Malik, Sweety (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Management of critically ill patients in obstetrics is a challenge owing to the changed physiology and unpredictability of the disease behaviour. Stratification strategy for early admission to obstetric ICU is imperative to reduce maternal morbidity and mortality. Due to lack of formal surveys regarding obstetrical ICU in our country, there is lack of precise national data on obstetrical ICU mortality. Aim of the present study was to estimate the obstetric ICU admission rate, to study the pattern of causative aetiology and to study the complications developed in ICU. Methods: The present study is a retrospective analytical study done in the Department of Obstetrics and Gynecology, from January 2015 to August 2017. Results: During the study period there were a total of 8466 obstetrical admissions, 2508 deliveries and 104 ICU admissions. Out of 104, analysis was done on 71 patients. Hypertensive disorders of the pregnancy were associated with maximum number of admissions (47.8%), followed by postpartum haemorrhage (12.6%). Maximum admissions were in postpartum period (63.4%). Anaemia was associated with 35.2% of the cases and it was closely followed by sepsis (28.2%). Mechanical ventilation was required for 30.9% of the patients. Conclusions: Hypertensive disorders of the pregnancy, haemorrhage and sepsis are the major risk factors for ICU admission in obstetric population.